Learning innovation tool for Sirah subject: Geosirah storymap tool. - Mohd Yusoff, Nur Syazwana; Mokhtar, Ernieza Suhana; Ahmad, Siti Zulaiha; Ismail, Ummi Syarah (Journal of Islamic, Social, Economics and Development, 2024)
Sirah, provide the history and timeline of a story in terms of dates, places, and events of the journey of our prophet, Nabi Muhammad S.A.W. However, most students showed a lack of interest because it only relies on extensive reading. Therefore, a group of lecturers and a postgraduate student from Universiti Teknologi MARA, Perlis, with the collaboration of Sekolah Menengah Agama Nurul Islam, Kedah, have organised a programme to introduce the GeoSirah Storymap application for secondary school students in the Sirah subject, which integrates geographical components. About 31 respondents from Sekolah Menengah Agama Nurul Islam, Kedah, joined and explored the application. To assess whether students have an interest in the application, the pre- and post-tests were distributed before and after application implementation, respectively. The findings of the programme through the distribution of pre-test and post-test showed a good effect, with a notable rise in the average rate of 23.44%. Moreover, the programme had a significant impact, as the result of the user acceptance test gained positive feedback among the students. This programme proved that GeoSirah Storymap can enhance students' cognitive understanding and comprehension levels for the Sirah subject, leading to increased interest and enjoyment in the subject matter.